2014
DOI: 10.1021/mp400768m
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization and Phase Changes in Paracetamol from the Amorphous Solid to the Liquid Phase

Abstract: For the case of paracetamol, we show how terahertz time-domain spectroscopy can be used to characterize the solid and liquid phase dynamics. Heating of supercooled amorphous paracetamol from 295 K in a covered sample under vacuum leads to its crystallization at 330 K. First, form III is formed followed by the transformation of form III to form II at 375 K, to form I at 405 K, and finally melting is observed around 455 K. We discuss the difference between the featureless spectra of the supercooled liquid and it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 49 publications
1
61
1
Order By: Relevance
“…131 Due to the high sensitivity of THz-TDS to intermolecular interactions, it was possible to determine the onset of crystallization very precisely and quantify the crystallization kinetics. Following the crystallization into form III, further phase transitions to forms II and I were observed before the sample melted.…”
Section: Crystalline Systemsmentioning
confidence: 99%
“…131 Due to the high sensitivity of THz-TDS to intermolecular interactions, it was possible to determine the onset of crystallization very precisely and quantify the crystallization kinetics. Following the crystallization into form III, further phase transitions to forms II and I were observed before the sample melted.…”
Section: Crystalline Systemsmentioning
confidence: 99%
“…According to these studies, the relaxation process and intermolecular stretching mode were observed. The dynamics of organic glass forming materials, such as polymers, poly-alcohols, sugars, and pharmaceutics, were investigated in the frequency of 0.2-3.0 THz using THz-TDS [16][17][18][19][20]. It is expected that the low-energy excitations of glassy materials such as a boson peak, intermolecular vibrations, and fast relaxation processes, can be studied by THz-TDS [21].…”
Section: Introductionmentioning
confidence: 99%
“…Refs. [8][9][10][11][12][13]. The sign of crystallization is a decrease in intensity of the signal, and the crystal fraction/concentration of the sample is often obtained by assuming that the relaxation strength is proportional to the volume fraction of liquid in the sample [14][15][16].…”
mentioning
confidence: 99%